2022
DOI: 10.1136/jitc-2022-004885
|View full text |Cite
|
Sign up to set email alerts
|

Baseline circulating unswitched memory B cells and B-cell related soluble factors are associated with overall survival in patients with clear cell renal cell carcinoma treated with nivolumab within the NIVOREN GETUG-AFU 26 study

Abstract: BackgroundThe phase II NIVOREN GETUG-AFU 26 study reported safety and efficacy of nivolumab in patients with metastatic clear cell renal cell carcinoma (m-ccRCC) in a ‘real-world setting’. We conducted a translational-research program to determine whether specific circulating immune-cell populations and/or soluble factors at baseline were predictive of clinical outcomes in patients with m-ccRCC treated with nivolumab within the NIVOREN study.MethodsAbsolute numbers of 106 circulating immune-cell populations we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…It has recently been reported that an increase in USM in the peripheral circulation is associated with IgG1/IgM responses to SARS-CoV2 results in earlier COVID-19 recovery ( 39 ). Furthermore, a parallel increase in circulating USM with cTfh has been reported in cancer patients who respond well to immune checkpoint therapy ( 40 ). Such an immune response in infection and cancer, in turn, potentially suggests an association between USM and cTfh in the autoimmune response in patients with NSA.…”
Section: Discussionmentioning
confidence: 92%
“…It has recently been reported that an increase in USM in the peripheral circulation is associated with IgG1/IgM responses to SARS-CoV2 results in earlier COVID-19 recovery ( 39 ). Furthermore, a parallel increase in circulating USM with cTfh has been reported in cancer patients who respond well to immune checkpoint therapy ( 40 ). Such an immune response in infection and cancer, in turn, potentially suggests an association between USM and cTfh in the autoimmune response in patients with NSA.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, unswitched memory cells are considered a non-classical type of memory B cells, and their origin in humoral immunity is controversial [21]. A related study investigated the impact of nivolumab on the treatment of renal clear cell carcinoma, and the results showed that unswitched memory cells played a positive role in the overall survival and progression-free survival of patients with renal clear cell carcinoma, this cell state is called the peripheral imprint of TME [22]. Our research provides a new perspective on PCa treatment by showing that unswitched memory B cells play a positive role in PCa risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-17A, a cytokine with a similar function to IL-6, was not similarly elevated in the non-HPD group after immunotherapy. IL-6, an immune inflammatory cytokine involved in immune cell development, has been shown to be associated with worse survival after treatment with anti-PD-1 therapy, 22 , 23 poorer treatment response, 24 and higher risk of immune-related adverse events. 25 IL-6 in the TiME is produced by cancer cells, host stromal cells, or tumor-infiltrating immune cells such as macrophages.…”
Section: Discussionmentioning
confidence: 99%